President Yudhoyono’s Response to Violence against Ahmadiyah and Shia: - A’an Suryana (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2016)
Abstract The era of President Susilo Bambang Yudhoyono saw rising intolerance and even violence against minority congregations, Ahmadiyah and Shia; in the forms of attacks to places of worships; attacks to houses belonging to minorities, forced eviction targeting minorities and banning against religious activities.This article looks at what factors that contributed to President Yudhoyono’s response to the rising violence against the minority congregations during his two terms at the office (between 2004 and 2014). Scholars criticized the president for his seemingly in action in addressing the violence. Some scholars argued it was the agency of President Yudhoyono that contributed to his indifference toward the violence. Other scholars pointed out at more structural factors that they argued to have caused President Yudhoyono for being indecisive, ignorant or slow in making actions toward the rising intolerance, such as his childhood experience and family background and the revival of corporatist metaphor in the post-New Order era that impeded the president for making bold measures to fight for the minority rights. Through the case study of President Yudhoyono’s response to the violence, the article aims to contribute to Indonesian perspective on the classic debate about whether structure shapes the agency, or agency shapes the structure. In light of the arguments that the scholars proposed in the preceding paragraph, I would argue that we need to think of beyond binary opposition between agency and structure. Scholars, especially the essentialists, had the habit to determinatively point out at either agents or structures, which were held responsible for the occurrence of events, but, omitting either factor would ignore some aspects that had the potentials to enrich our understandings about what motivates the agents in making social actions. Keywords: Violence, Ahmadiyah, Shia, Minority Rights.